Air Quality Monitoring and Decision Support System Using IoT - Agus Alwi Mashuri (Politeknik Negeri Semarang, 2021)
Air is one of the most important elements of life for living things in the world. For humans, the air is an element that is very concerned because it is related to health. In Jakarta, the Air Pollution Standard Index (ISPU) is ranked second as the capital city of a country with poor air quality. Air quality in Jakarta is monitored by an Air Quality Index (AQI) of 160 with parameters in the form of very small pollutant particles with a diameter of fewer than 2.8 micrometres (PM 2.8). The purpose of this research is how we make a tool that can determine the quality of the air around us and can be carried (portable) anywhere easily. In accordance with the 4.0 industrial revolution that everything has been integrated with the Internet of Things (IoT) technology where the public can find out the air condition in real-time. In this study, the prototype method is used as a test. The main components are sensors consisting of MQ-6 (CO2 and smoke), MQ-7 (CO, LPG, CH4), MQ135 (Butane, AirQuality), and DHT-11 (Humidity, temperature). From the research that has been done where the air quality in urban areas has a low air quality index by measuring it using a prototype consisting of a gas sensor and Arduino microcontroller, which has been made to produce an average CO2 of 25 ppm, CO 2330 which has exceeded the threshold, while NH3 1.23 and C4H10 1120 are still below the threshold. These values are influenced by pollutants generated by transportation such as motorbikes, cars, and land transportation